Contested Kinship and the Dispute of Customary Law in Colonial Kenya - Holmes, J. Teresa (Anthropologica, 2022)
In the 1930s, individuals claiming membership in the dispersed Luo Ugenya Kager clan and the local officials of the British colonial administration were actively disputing Native rights to land and authority in a region of the central Nzoia River valley of western Kenya. In this article I argue that this dispute was part of a larger discursive process in which both colonizer and colonized participated. This process is seen as one in which colonizing agents invented clan-based tribal forms that privileged agnatic principles of customary law, while "Kager" peoples utilized alternative notions of kin-based rights to land and authority in an attempt to construct meaningful forms of community identity.